1993
DOI: 10.1093/clind/16.4.534
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Levels of Tumor Necrosis Factor-  and Interleukin-1  in the CSF of Patients with Meningitis of Different Etiologies: Utility in the Differential Diagnosis

Abstract: We assayed tumor necrosis factor-alpha (TNF-alpha) and interleukin-1 beta (IL-1 beta) concentrations in CSF from patients with meningitis of different etiologies and tested the usefulness of these assays for differentiating between pyogenic meningitis and aseptic meningitis of different etiologies. We used a monoclonal-antibody ELISA to test 125 CSF specimens from patients whose cases were classified as follows: pyogenic meningitis (n = 20), viral meningitis (n = 22), self-resolving aseptic meningitis for whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…10,12 Lopez-Cortes and colleagues 11 found that CSF levels of tumor necrosis factor-␣, IL-1␤, IL-6, and IL-8 were significantly higher in neurosurgical patients with bacterial meningitis than in patients with asymptomatic aseptic meningitis. These inflammatory cytokines are synthesized intrathecally by activated leukocytes 7,24 and were found to be more specific predictors of bacterial meningitis, compared with cell counts, in the study by Lopez-Cortes and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Lopez-Cortes and colleagues 11 found that CSF levels of tumor necrosis factor-␣, IL-1␤, IL-6, and IL-8 were significantly higher in neurosurgical patients with bacterial meningitis than in patients with asymptomatic aseptic meningitis. These inflammatory cytokines are synthesized intrathecally by activated leukocytes 7,24 and were found to be more specific predictors of bacterial meningitis, compared with cell counts, in the study by Lopez-Cortes and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the subarachnoid space, where the principal humoral and cellular host defense mechanisms are absent (432,555), meningococci proliferate uncontrolled (57). The evolving endotoxin liberation elicits compartmentalized (i.e., confined to the subarachnoid space) activation of proinflammatory cytokines such as TNF, IL-1, IL-6, IL-8, nitric oxide, monocyte colony-stimulating factor, and platelet-activating factor and anti-inflammatory cytokines such as IL-1Ra, IL-10, IL-12, TNFsR-p55, TNFsR-p75, and IL-1sR type II (IL-1sRII) (12,57,192,264,295,429,498,502,517,(519)(520)(521). Among these, TNF and IL-1 enhance the permeability of the blood-brain barrier and promote the influx of neutrophils by upregulation of adherence molecules (258,374,377,428).…”
Section: Pathophysiology Of Meningococcal Meningitismentioning
confidence: 99%
“…However, the vaccine had little impact on the incidence of bacterial meningitis at large (8,9). TNF-a has been detected in the cerebrospinal fluid (CSF) of the majority of patients with bacterial meningitis and in some patients with viral forms (10)(11)(12). Furthermore, CNS damage in the course of bacterial meningitis correlates with the extent of the inflammatory response in the subarachnoid space (13,14).…”
mentioning
confidence: 99%